2010
DOI: 10.1016/j.apenergy.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of forest biomass for use as energy. GIS-based analysis of geographical availability and locations of wood-fired power plants in Portugal

Abstract: a b s t r a c tFollowing the European Union strategy concerning renewable energy (RE), Portugal established in their national policy programmes that the production of electrical energy from RE should reach 45% of the total supply by 2010. Since Portugal has large forest biomass resources, a significant part of this energy will be obtained from this source. In addition to the two existing electric power plants, with 22 MW of power capacity, 13 new power plants having a total of 86.4 MW capacity are in construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 10 publications
(13 reference statements)
2
79
0
9
Order By: Relevance
“…Availability factor (w) is the relationship between the mass of available biomass (m) and the mass of total biomass (M) in the collection area under technoeconomical and environmental constrains; this is calculated from (1). m = w · M…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability factor (w) is the relationship between the mass of available biomass (m) and the mass of total biomass (M) in the collection area under technoeconomical and environmental constrains; this is calculated from (1). m = w · M…”
Section: Methodsmentioning
confidence: 99%
“…The EU believes that biomass for power and heat production can play a leading role by the year 2020, when greenhouse gas emissions should have been reduced by 20%, renewable energy sources should represent 20% of final energy consumption and energy efficiency should have increased by 20% [1]. Emissions of anthropogenic origin, which mostly contribute to the greater concentration of CO 2 , come from using and consuming fossil fuels for domestic and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The energy produced using corn stover and forest logging residue was calculated for each county. Viana [23] found that a typical CHP plant operated for a total of 8000 h a year or 333 days a year. For this study, the CHP plants in Scott and Washington counties were assumed to be in operation 24 h a day, 340 days a year and 8160 h per year.…”
Section: Biomass Conversionmentioning
confidence: 99%
“…The logging residue results from a silvicultural activity, namely forest thinning and harvesting. Information about the potential residual log can be used for making decisions in forest management, such as fuel management for forest fire (van Wagner 1968), evaluate forest harvesting activity (Grushecky et al 2007;Ghaffariyan et al 2013), estimation of the effectiveness of forest harvesting (Budiaman & Komalasari 2012;Matangaran & Anggoro 2012), utilization of residual log for bioenergy (Smeets & Faaij 2007;Viana et al 2010;Okello et al 2013), monitoring of forest ecosystems (Helmisaari 2011;Smolander et al 2013), and assessment of forest ecosystem services (Sikkink & Keane 2008;Woodall et al 2008). As result, accurate information of logging residue inventory is needed to support sustainable forest management (Tiryana et al 2011;Bouriaud et al 2013).…”
Section: Introductionmentioning
confidence: 99%